Radicular Cyst Masquerading as a Periapical Abscess: A Case Report - Gupta, Kajal; Baruah, Pranami; Tandon, Sapna; Chauhan, Himanshu; Tripathi, Anjali; Agrawal, Ambhuja (Journal of Neonatal Surgery, 2025)
Background: Most of the inflammatory odontogenic cysts are radicular cysts, which are usually found incidentally on radiographs unless they are secondary infections and are often linked to non-vital teeth. Introduction: After pulpal necrosis from trauma or caries, these cysts usually develop as a result of persistent periapical inflammation. Larger lesions can cause swelling, pain, or discharge, but they are typically asymptomatic. Two patients with anterior maxillary radicular cysts who both had a history of trauma are the subject of this case study. The diagnosis was made based on aspiration, radiographic results, and clinical evaluation. Apicectomy, surgical enucleation, root canal therapy, and the application of platelet-rich fibrin (PRF) to aid in healing were all part of the management. Conclusion: In conclusion, these cases demonstrate how important it becomes to thoroughly evaluate patients with dental trauma both clinically and radiographically. A customized endodontic and surgical treatment plan combined with early diagnosis can may assure the lesion's full healing while avoiding complications. This includes PRF facilitates tissue regeneration and healing. In order to effectively manage radicular cysts and maintain both function and aesthetics, a multidisciplinary approach is still essential.